Healthy sleep without insomnia may go beyond sleep duration for achieving successful aging in Chinese older adults: a cross-sectional study - Yibing Liu; Jingang Ji; Wenwen Du; Qiuye Cao; Chang Su; Yuna He; Huijun Wang; Xiaofang Jia (BMC Geriatrics)
Abstract Objective Successful aging (SA) is a major challenge of population aging. Exploring modifiable factors becomes the focus of promoting SA. We aimed to understand SA status and determine association between sleep and SA in China. Methods Present study targeted subjects aged ≥ 60 years and those with completed data of demographics, lifestyle, disease history, physical and mental health, and anthropometrics in China Health and Nutrition Survey 2018. Sleep was evaluated using self-reported sleep duration and Bergen insomnia scale. SA was assessed from overall health, mental and cognitive health, activities of daily life, and physical capacity. Multivariate logistic regression models were employed to examine association between sleep and SA and its components. Restricted cubic spline regression models were applied to explore dose-response relationships between insomnia score/sleep duration and SA. Results About 41.29% subjects achieved SA. Compared to reference of having no insomnia or having 7–8 h of sleep daily, subjects with insomnia and those with ≥ 9 h of sleep had decreased odds of SA by 53% and 18%, respectively (p < 0.05). Relative to subjects with 7–8 h sleep per day (meaning optimal sleep duration) and without insomnia, those having optimal sleep duration but suffering from insomnia (OR = 0.50, 95%CI:0.39–0.62), improper sleep duration ruling out 7–8 h of sleep but without insomnia (OR = 0.84, 95%CI:0.73–0.97), and both improper sleep duration and insomnia (OR = 0.40, 95%CI:0.32–0.50) displayed lower odds of SA. There were nonlinear dose-response relationships between sleep indicators and SA, that was concave-up for insomnia score while inverted U-shape for sleep duration, where inflection points indicating rapidly decreased SA odds were 2.95 points of insomnia and 8 h sleep duration daily. Conclusions Insomnia and longer sleep duration are negative factors for SA in Chinese older adults, and good sleep quality indicated by no insomnia seems more important than sleep duration for SA.